Gender stereotyping in medical interaction: A Membership Categorization Analysis. Issue 11 (November 2022) - Stommel, Wyke; Plug, Ilona; olde Hartman, Tim C.; Lucassen, Peter L.B.J.; van Dulmen, Sandra; Das, Enny
Abstract: Objective: Gender can be a valuable resource in communication but also a problem, perpetuating gender stereotypes. So far, there has been little attention for how healthcare professionals and patients make gender relevant in medical interactions. The approach of Membership Categorization Analysis (MCA) is particularly pertinent to meticulously analyze gender in medical communication. Applying MCA, this study analyzes how activity descriptions implicitly associated with gender stereotypes, e.g., "carrying a laundry basket up the stairs", feature in the course of GPs' explanations of a question or diagnosis. The aim is to provide a new perspective on the relationship between gender and medical interaction, and to increase our understanding of how gender stereotypes are reproduced in the medical setting. Method: Two cases of GPs using gendered explanations in Dutch general practice interactions are analyzed turn-by-turn using MCA. Results: The findings show how GPs' descriptions of gendered activities serve the exemplification of technical terms, designed for the specific patient, while also casting the patient in a traditional gender role. Conclusion: Invoking gender in medical interaction may serve a communicative goal while also perpetuating stereotypes. Practice implications: Insight in the subtleties of gender construction in medical interactions could enhance gender awareness and sensitivity in healthcare. Highlights: MCA provides insights in gender as a social construct in medical interactions. GPs use gendered activities from everyday life to explain technical terminology. By reference to gendered activities GPs unnecessarily 'gender' their patients. Insights in how gender work is done may enhance gender awareness in health care.